A Review of Supportive Interventions Targeting Individuals or Couples Undergoing Infertility Treatment: Directions for the Development of Interventions. Issue 6 (17th August 2016) - Luk, Bronya Hi-Kwan; Loke, Alice Yuen
Abstract : The purpose of this systematic review is to explore the types, content, and outcomes of different psychosocial approaches used in existing interventions for infertile individuals or couples. Relevant intervention studies published in English between 2000 and 2014 were searched using the electronic databases MEDLINE, PsycINFO, and CINHAL Plus. A total of 23 articles were identified and included in this review. Cognitive behavioral therapy (CBT), acceptance and commitment therapy (ACT), and counseling were the most commonly adopted psychosocial interventions for infertile individuals or couples. After reviewing the various approaches, directions are given on the development of interventions for couples suffering from infertility.